Abnormal lung lymphatics and respiratory failure. Issue 5 (May 1989) - Moss, S F; Currie, D C; Sheffield, E A; Baxter, M; Corrin, B; Evans, T W
Abstract : A 65 year old man presented with respiratory failure, pleural effusions, fine reticulonodular shadowing on a chest radiograph, and severe impairment of carbon monoxide diffusing capacity (transfer factor). Open lung biopsy showed only dilated pleural and subpleural lymphatic channels. Hypoplastic deep pulmonary lymphatics may have led to respiratory failure.